2008
DOI: 10.1021/cm800518x
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Controlled Synthesis of FeCo Nanocubes and Microcages by Wet Chemistry

Abstract: Nanocubes and hollow cubic microcages of FeCo alloy have been synthesized in large scale by reduction of aqueous Fe 2+ and Co 2+ with hydrazine in the presence of poly(ethylene glycol) and cyclohexane at a relative low temperature, which were confirmed by X-ray powder diffraction, transmission electron microscopy, and scanning electron microscopy. The morphology and dimensions of FeCo alloy nanocrystals could be controlled by the reaction conditions such as the concentrations of cyclohexane and PEG-400, reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 71 publications
5
61
0
Order By: Relevance
“…6 that the saturation magnetization (M s ) of the three samples increases with the rising of reaction temperature, which may be ascribed to a variation of Fe/Co ratio in the samples. It has been found that the M s values of the FeCo alloys are determined using the Fe/Co ratio in bcc FeCo phase and generally increase with higher concentration of Fe to some extent [15,30]. As can be seen, the large-grain FeCo particles with ideal microstructure and optimal magnetic properties can be obtained by controlled chemical synthesis.…”
Section: Resultsmentioning
confidence: 96%
“…6 that the saturation magnetization (M s ) of the three samples increases with the rising of reaction temperature, which may be ascribed to a variation of Fe/Co ratio in the samples. It has been found that the M s values of the FeCo alloys are determined using the Fe/Co ratio in bcc FeCo phase and generally increase with higher concentration of Fe to some extent [15,30]. As can be seen, the large-grain FeCo particles with ideal microstructure and optimal magnetic properties can be obtained by controlled chemical synthesis.…”
Section: Resultsmentioning
confidence: 96%
“…Among the candidates, FeCo alloys, the outstanding soft-magnetic materials, have attracted great interest due to the high saturation magnetization (up to 2.45 T), low magnetostriction, high resistivity, small coercive forces and high Curie temperature [5][6][7]. FeCo composites, such as Y 2 O 3 /FeCo shell/core nanocomposites [8], Al 2 O 3 and C-coated FeCo nanocapsules [9,10], have been developed and an expected microwave absorption ability is obtained because of a better electromagnetic match.…”
Section: Introductionmentioning
confidence: 99%
“…The observed saturation magnetization values for the samples S1 and S2 are 141.8 and 104.9 emu/g respectively. These values are significantly reduced as compared to that of their bulk values Fe 50 Co 50 (211 emu/g) [15]. The reasons for the reduction of saturation magnetization are decrease in iron content in the samples i.e.…”
Section: Resultsmentioning
confidence: 86%
“…Synthesis of Fe-Co nanoparticles by polyol process is successful in controlling the size and morphology [8]. Fe-Co nanoparticles with a variety of morphologies such as spherical [8], dice [9], microcages [15], hollow spheres [16] and acicular [17] have been synthesized through chemical methods. When compared to other chemical synthesis techniques, polyol process is the best one for fine tuning the morphology of the synthesized nanoparticles [18].…”
Section: Introductionmentioning
confidence: 99%